2008
DOI: 10.1681/asn.2007050531
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-Stimulated SGK1 Activity Mediates Profibrotic Signaling in the Mesangium

Abstract: Several recent reports support the hypothesis that aldosterone contributes to the progression of renal injury. Mineralocorticoids increase the expression of serum-and glucocorticoid-inducible protein kinase 1 (SGK1), which is upregulated in several fibrotic diseases. It was hypothesized that SGK1 may mediate the effects of aldosterone on glomerular fibrosis and inflammation. In primary cultures of rat mesangial cells, aldosterone stimulated the expression, phosphorylation, and kinase activity of SGK1, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 50 publications
4
55
0
3
Order By: Relevance
“…Recent studies reported that stimulation of NF-B-dependent luciferase reporter gene activity by aldosterone is dependent on SGK1 in glomerular mesangial cells and in fibroblasts. 11,12 Moreover, SGK1 has been shown to associate physically with and phosphorylate IKK␤, 22 which, once activated, phosphorylates p65/RelA. 33 In agreement with these findings, our results indicate that knockdown or overexpression of SGK1, respectively, inhibited or increased NF-B-targeted gene expression in response to aldosterone.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Recent studies reported that stimulation of NF-B-dependent luciferase reporter gene activity by aldosterone is dependent on SGK1 in glomerular mesangial cells and in fibroblasts. 11,12 Moreover, SGK1 has been shown to associate physically with and phosphorylate IKK␤, 22 which, once activated, phosphorylates p65/RelA. 33 In agreement with these findings, our results indicate that knockdown or overexpression of SGK1, respectively, inhibited or increased NF-B-targeted gene expression in response to aldosterone.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, aldosterone-induced NF-B activation is not restricted to nonepithelial cells, such as mesangial cells or fibroblasts, as described previously, 11,12 but is also observed in epithelial CD principal cells.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Aldosterone/MR induces phosphorylation of serum and glucocorticoid regulated kinase 1 (SGK1), which in turn phosphorylates and inactivates the nuclear factor of κ light polypeptide B, resulting in the activation of nuclear factor κB (NFκB) (27,30). The activated NFκB then enhances the transcription of inflammatory cytokine genes such as intercellular adhesion molecule 1 and connective tissue growth factor (CTGF) (30).…”
Section: Aldosterone/mr and Inflammation In The Kidneymentioning
confidence: 99%